10 Tip-Apex Distance in DHS & IM Nail Fixations for Hip Fractures. (28th February 2022) - Tan, G.; Ong, C.T.; Kainth, G.
Abstract: Aim: Dynamic hip screws (DHS) and intramedullary nail (IMN) fixations have been successful in treating extracapsular hip fractures. Tip to apex distance (TAD) is defined as the total sum of distance from tip of the lag screw to the femoral head tip on both AP and lateral radiographs. Baumgartner et al. defined TAD<25 mm to be predictive of a successful result, with reduced rates of metalwork failure. Therefore, this study aims to assess if TAD principles are practiced during DHS and IMN fixations. Method: 102 patients were identified between December 2019 and February 2020. The distance was measured on AP and lateral radiographs to calculate the TAD. Patients were followed up for 1 year where the fractures either united or failed. Results: Patients recruited had age ranges between 19–103 years old, of which 36% are male and 64% are female. 68% had underwent DHS while 32% underwent IM nail. In the DHS group, 13 patients had TAD of >25 mm, 28 with TAD of 20–25 mm, 18 with TAD of 15–20mm and 6 with TAD of <15 mm. For the IM nail group, there are 7 with TAD of 20–25 mm, 13 with TAD of 15–20mm and 10 with TAD of <15 mm. Conclusions: There were no IM nails that exceeded TAD of 25mm, but 13 DHS fixations were >25mm. 12/13 DHS fixations >25mm TAD were performed by trainees. We advocate emphasis on the TAD principle and re-enforcing to orthopaedic trainees to improve the outcome of DHS in patients with neck of femur fractures.